Azido chelating fiber: synthesis, characterization and adsorption performances towards Hg2+ and Pb2+ from water. (14th February 2017) - Zhang, Like; Wang, Yanan; Huang, Jiajia; Yuan, Siguo
Abstract : Herein, we report the synthesis and adsorption property of a novel chelating fiber containing azido group. Firstly, the brominated fiber (PP‐St‐DVB‐Br) was obtained via the reaction of polypropylene‐(g)‐styrene‐divinylbenzene fiber (PP‐St‐DVB) with bromine in CH2 Cl2 solution. Then, azido chelating fiber (PP‐St‐DVB‐N3 ) was prepared by azidation of PP‐St‐DVB‐Br fiber. Its structure and properties were characterized by Fourier transform infrared, elemental analysis, thermogravimetric analysis, and chemical titration, respectively. The micromophology and functional group distribution in fibrous matrix were investigated by scanning electron microscopy‐energy dispersive spectroscopy. The results show that the chelating fiber has high functional group contents (2.11 mmol/g for PP‐St‐DVB‐N3 ) and uniform distribution. Different from granulate chelating resin, the novel fibrous adsorbent possesses excellent adsorption ability for Hg(II) and Pb(II) ions (408.9 mg/g for Hg 2+ and 334.4 mg/g for Pb 2+ ), and the adsorption capacity of the fiber has no loss until five cycles. The novel absorbent material shows the potential application prospect in the treatment of heavy metal wastewater. Copyright © 2017 John Wiley & Sons, Ltd.